2013
DOI: 10.4238/2013.september.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of the interleukin-28B gene polymorphism with development of hepatitis virus-related hepatocellular carcinoma and liver cirrhosis: a meta-analysis

Abstract: ABSTRACT. We examined the association of the interleukin-28B (IL-28B) gene rs12979860 T/C polymorphism with development of hepatitis virus-related hepatocellular car cinoma (HCC) and liver cirrhosis (LC). Two investigators independently searched the PubMed, Elsevier, EMBASE, Web of Science, Wiley Online Library, and Chinese National Knowledge Infrastructure data bases. Pooled odds ratios (ORs) and 95% confidence intervals (95%CIs) for rs12979860 and HCC/LC were cal culated in a fixed-effect model (the Mantel-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Our study demonstrates that microvascular invasion was a risk that increased HCC recurrence and affected the prognosis of HCC patients, which is consistent with previous findings [6,26,27]. A close relationship between cytokines and HCC has been reported in recent years [28][29][30][31]. IL6 is a crucial effector cytokine that is involved in hepatic physiology, including hepatoprotection, the acute-phase response, and mitogenesis in liver regeneration [11,32].…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrates that microvascular invasion was a risk that increased HCC recurrence and affected the prognosis of HCC patients, which is consistent with previous findings [6,26,27]. A close relationship between cytokines and HCC has been reported in recent years [28][29][30][31]. IL6 is a crucial effector cytokine that is involved in hepatic physiology, including hepatoprotection, the acute-phase response, and mitogenesis in liver regeneration [11,32].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, one study found a significant association with cirrhosis, although most studies using cirrhosis or fibrosis as an outcome did not find an association. Four of the studies were meta‐analyses, with three of these focusing on rs12979860 and HCC and one focusing on fibrosis. Of these, two meta‐analyses found a positive association between rs12979860 and HCC and one found an association between fibrosis and rs12979860.…”
Section: Resultsmentioning
confidence: 99%
“…The variations in association of SNPs among studies conducted on Pakistani patients may have been due to different ethnic background of the patients. The polymorphism rs12979860 CT genotype has been associated with hepatocellular carcinoma and liver cirrhosis in seven different studies conducted previously on 1152 patients [Suo and Zhao, ]. In the cohort of 120 nonresponder patients, 59.1% (71/120) patients were in stage 2 of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The IL28B rs12980275 AA genotype on the other hand, was found to be associated with sustained virological response in Chinese patients with HCV genotype 1 or genotype 6 [Zhang et al, ]. It has also been disclosed that the genotypes of rs12979860 have been associated with development of hepatocellular carcinoma and liver cirrhosis after HCV infection [Suo and Zhao, ].…”
Section: Introductionmentioning
confidence: 99%